Prospective epidemiological study of juvenile-onset systemic lupus erythematosus in the UK and Republic of Ireland. (3rd February 2022) - Lythgoe, Hanna; Smith, Eve M D; Killeen, Orla G; Murphy, Ruth; Pilkington, Clarissa; Pain, Clare E; Beresford, Michael W; ,
Abstract: Objectives: The primary objective was to define the incidence of JSLE in children <16 years of age in the UK and Republic of Ireland (ROI). The secondary objective was to describe presenting features, classification criteria, initial management and disease damage in newly presenting JSLE patients. Methods: A prospective JSLE epidemiological study was undertaken between September 2017 and September 2019 with support of the British Paediatric Surveillance Unit and other professional groups involved in diagnosis and management of JSLE patients. Treating consultants reported all cases of JSLE seen. A follow-up study at 1 year examined management and progression of disease and treatment. Results: There were 124 incident cases included in the final analysis. Incidence was estimated using ACR-1997 classification criteria (0.36/100 000), SLICC-2012 classification criteria (0.41/100 000) and clinician expert opinion (0.46/100 000). A high disease burden was seen, with 71.0% of patients requiring ongoing systemic CS treatment at 1 year; 98.2% receiving immunomodulatory treatment; and 20.4% accruing damage in the year following diagnosis (predominantly neuropsychiatric-related), with substantial involvement from multiple speciality teams. Conclusions: The minimum UK and ROI incidence of JSLE is between 0.36 and 0.46/100 000, depending on the case definition used. Challenges in classification of patients with JSLE are highlighted, but overall this study supports the use of SLICC-2012 classification criteria. The high levels of disease damage and ongoing CS use 1 year after diagnosis is concerning, highlighting the need for further interventions to improve outcomes in JSLE.